Comparative characteristic of morphological peculiarities of linseed varieties in conditions of Right-Bank Forest-Steppe of Ukraine - Столярчук, Т. А.; Кисильчук, А. М. (Scientific Progress & Innovations, 2017)
Linseed varieties are of great importance for obtaining stable yields of high quality. However, for linseed, there is a significant variability in the signs of seed productivity (amount and mass of seeds from the plant, mass of 1000 seeds) and biochemical composition of the seeds, but information about genotypic potential realization of the culture is limited. It is because of this variability of linseed characteristics our study was aimed at comparing morphology of plants different varieties during cultivation precisely in conditions of the Right-bank Forest-Steppe of Ukraine. Studies have shown that growing conditions affect on such genotypic signs as height of the plants and number of fruitcases on the plant. Weight of 1000 seeds and number of seeds in the fruitcase is relatively stable and has insignificant variability. Weight of the seeds from one plant depends from number of fruitcases on the plant, as evidenced by the high correlation coefficient. The biggest height of the plants during the all years of research has variety Liryna, the shortest – variety Aisberg. The highest weight of 1000 seeds has variety Pivdenna nich. The best by productivity of the one plant in conditions of Right-bank Forest-Steppe of Ukraine were varieties Evryka, Lirina and Blakytno-pomaranchevyi.